Antidepressive Mechanisms of Probiotics and Their Therapeutic Potential - Yong, Shin Jie; Tong, Tommy; Chew, Jactty; Lim, Wei Ling (Frontiers in Neuroscience, 2020)
The accumulating knowledge of the host-microbiota interplay gives rise to the microbiota-gut-brain (MGB) axis. The MGB axis depicts the interkingdom communication between the gut microbiota and the brain. This communication process involves the endocrine, immune and neurotransmitters systems. Dysfunction of these systems, along with the presence of gut dysbiosis, have been detected among clinically depressed patients. This implicates the involvement of a maladaptive MGB axis in the pathophysiology of depression. Depression refers to symptoms that characterize major depressive disorder (MDD), a mood disorder with a disease burden that rivals that of heart diseases. The use of probiotics to treat depression has gained attention in recent years, as evidenced by increasing numbers of animal and human studies that have supported the antidepressive efficacy of probiotics. Physiological changes observed in these studies allow for the elucidation of probiotics antidepressive mechanisms, which ultimately aim to restore proper functioning of the MGB axis. However, the understanding of mechanisms does not yet complete the endeavor in applying probiotics to treat MDD. Other challenges remain which include the heterogeneous nature of both the gut microbiota composition and depressive symptoms in the clinical setting. Nevertheless, probiotics offer some advantages over standard pharmaceutical antidepressants, in terms of residual symptoms, side effects and stigma involved. This review outlines antidepressive mechanisms of probiotics based on the currently available literature and discusses therapeutic potentials of probiotics for depression.